AB1245-HPR New health technologies and lifestyle management for patients with osteoarthritis. (15th June 2017) - Loiskandl, M; Ritschl, H; Stamm, T; Steiner, G; Smolen, J; Aletaha, D
Abstract : Background: Osteoarthritis (OA) is one of the most common chronic diseases of the elderly worldwide. It represents significant impairments in terms of quality of life [1]. It notably affects self-care-tasks, body-image, self-esteem, well-being, social-activities and relationships. A wide-ranged field of therapy concepts exist. Medication is often one part, but it cannot solve other existing problems due to OA [2]. The demographic trends combined with the growth of mobile devices among the older population suggest that using digital devices, as a platform for interventions in health, may be a viable way forward and open new opportunities in healthcare [2]. Objectives: To (A) analyse the literature to assistive devices and applications for OA patients and (B) to evaluate existing health applications. Methods: We performed a systematic literature review on this topic and explored existing mobile and web-based apps. The app findings were classified into those categories of the Activities of Daily Living Model, which were related to the impairments of OA. Results: We identified 6 studies, which contained relevant information. The main results showed, that there is interest and willingness to utilize mobile Health solutions [3]; a positive impact of web-based interventions; the benefit of online social support regarding the level of patient empowerment [4], self-management, lifestyle, physical activity [5] and self-efficacy [6]. The app exploration results in 16 web-based, 15 iOS and 9 Android applications. The areas most commonly found were disease- and treatment information (n=23), forum, report, self-help groups (n=16), self- and disease-management (n=11), as well as nutrition tips (n=8). Conclusions: The recent years have seen a dramatic growth of digital applications. Also, the scientific interest has grown and numerous studies emphasise the power of these solutions to support OA patient in all areas of lifestyle management. Further research is necessary, to investigate the benefit of web-based or mobile applications for persons with OA. References: T. Aigner, S. Söder, Typisierung, Graduierung und Stadieneinteilung der Osteoarthrose: Histopathologische Begutachtung der Gelenkdegeneration, Z. Für Rheumatol., 2008;67(1):32–40. J. Joe, G. Demiris, Older adults and mobile phones for health: A review, J. Biomed. Inform. 2013;46(5):947–954. S.J. Parker, S. Jessel, J.E. Richardson, M.C. Reid, Older adults are mobile too!Identifying the barriers and facilitators to older adults' use of mHealth for pain management, BMC Geriatr. 2013;13(1):43. A. Allam, Z. Kostova, K. Nakamoto, P. J. Schulz, The Effect of Social Support Features and Gamification on a Web-Based Intervention for Rheumatoid Arthritis Patients: Randomized Controlled Trial, J. Med. Internet Res. 2015;17(1):e14. H. Umapathy, K. Bennell, C. Dickson, F. Dobson, M. Fransen, G. Jones, D.J. Hunter, The Web-Based Osteoarthritis Management Resource My Joint Pain Improves Quality of Care: A Quasi-Experimental Study, J. Med. Internet Res. 2015;17(7):e167. K.R. Lorig, P.L. Ritter, D.D. Laurent, K. Plant, The internet-based arthritis self-management program: A one-year randomized trial for patients with arthritis or fibromyalgia, Arthritis Rheum. 2008;59(7):1009–1017. Disclosure of Interest: None declared